FDI-flows and reinvested earnings: Measurement, perceptions and pitfalls in interpretation - Gábor Obláth (Hungarian Academy of Sciences, Institute of Economics, 2017)
The study addresses methodological and conceptual issues related to the measurement, perception and economic interpretation of FDI (foreign direct investment) flows, focusing on reinvested earnings (RE). Using Hungarian data for the period 2008-2014 as an example, we review the effects of two internationally endorsed methodological revisions affecting the interpretation and quantification of RE. The reason for relying only on Hungarian data is that other countries do not disclose information on quantitative effects of the methodological changes. The empirical importance of the revision introduced in 2008 is attested by the fact that while the present methodology indicates a net FDI inflow of 10.5 billion euros, the one applied until 2007 would suggest a cumulative net outflow of 5.6 billion euros from Hungary in the period 2008-2014. The huge difference between the two is hidden in statistics on the international investment position (IIP) of the country, which is beyond the focus of most analysts. Although the revisions resulted in the congruence of statistical data with economic concepts of FDI income and RE, they may have become less expressive of the decisions and behaviour of foreign investors. In addition, the revisions lead to breaks in national time series and raise questions regarding the comparability of data across countries. For comparisons over time and between countries, we recommend the use of data on changes in (net) FDI stocks, unaffected by the methodological revisions.
Keywords: E01; F21; F23; F29; 330; FDI flows and stocks; reinvested earnings; statistical measurement; methodological revisions